Nilai Moral sebagai Prediktor Orientasi Politik pada Anggota Organisasi Keagamaan - Irfan Fahmi; Bagus Takwin; Roby Muhamad (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This study aims to examine the relationship of moral values formed in five moral values, harm/care, fairness/ reciprocity, ingroup/loyalty, authority/respect and purity/sanctity with the political orientation of the various Islamic organizations in Indonesia. Research carried out by the quantitative method with the correlational approach. Participants in this study were 531 Muslims who affiliated the Nahdlatul Ulama (NU), Muhammadiyah, Persis, Mathlaul Anwar, PUI, LDII, and Hizb ut-Tahrir Indonesia (HTI). The results show that Muslim organizations in Indonesia showed different patterns in the moral values that associated with the political orientation of Islam. Based on this research Nahdlatul Ulama (NU), Muhammadiyah, Mathlaul Anwar, PUI, and LDII including Islamic groups with a political orientation inclusive while Persis and Hizb ut-Tahrir Indonesia (HTI), including the Islamic group with exclusive political orientation.